PENGARUH CORPORATE GOVERNANCE TERHADAP STOCK RETURN SYNCHRONI CITY PERUSAHAAN SEBAGAI BENTUK TRANSPARANSI DI MASA YANG AKAN DATANG PADA SEKTOR CONSUMER GOODS DI BURSA EFEK ASEAN PERIODE 2011-2015 - CHRISTHA MEIRIN D.S.; Werner Ria Murhadi; Bertha Silvia Sutejo (CALYPTRA, 2018)
The objective of this research is to examine the effect of board size, board independence, audit quality, institutional ownership, market to book ratio, standard deviation of stock return and standar deviation of return on asset as the independent variable to stock return synchroniciry as a measure of corporate transparency as the dependent variable on the consumer goods sector that listed on the ASEAN (Indonesia, Malaysia, Thailand and Singapore) Stock Exchange 2011-2015 period. This research uses quantitative perspective with linier regression and Partial Adjustment Model in a panel data for all of the research’s observation that used in this research. The number of observation in this research are 385 observations, consist of 77 firms (25 firms from Indonesia, 17 firms from Malaysia,21 firms from Thailand, 14 firms from Singapore) that enlisted for 2011-2015 period. The result shows that board size and board independences have negative significant effect to stock return synchronicity. Then, institutional ownership, market to book ratio and standard deviation of stock return have positive significant effect to stock return synchronicity. Meanwhile, audit quality and standard deviation of return on asset have no effect to stock return synchronicity.